(untitled) (MAUSAM, 1967)
A study of the results of five years of observations of downward atmospheric radiation and net atmospheric radiation at New Delhi from 1958-1962 has been made. Downward atmospheric radiation is maximum during the cloudy monsoon months and minimum during winter, High values occur also in winter associated with Western Disturbances and summer due to increased dust content in the atmosphere. Net radiation is maximum during the cloud free winter and summer months and minimum during the cloudy months, Due to the continental semi-arid character of its climate and the extreme dryness of the atmosphere over Delhi the annual variations in both downward and net atmospheric radiation are compared to those at Madras except during the monsoon months.